Central urocortin 3 and type 2 corticotropin-releasing factor receptor in the regulation of energy homeostasis: critical involvement of the ventromedial hypothalamus - Chen, Peilin; Van Hover, Christine; Lindberg, Daniel; Li, Chien (Frontiers in Endocrinology, 2013)
The vital role of the corticotropin-releasing factor (CRF) peptide family in the brain in coordinating response to stress has been extensively documented. The effects of CRF are mediated by two G-protein coupled receptors, type 1 and type 2 CRF receptors (CRF1 and CRF2). While the functional role of CRF1 in hormonal and behavioral adaptation to stress is well known, the physiological significance of CRF2 remains to be fully appreciated. Accumulating evidence has indicated that CRF2 and its selective ligands including Urocortin 3 (Ucn 3) are important molecular mediators in regulating energy balance. Ucn 3 is the latest addition of the CRF family of peptides and is highly selective for CRF2. Recent studies have shown that central Ucn 3 is important in a number of homeostatic functions including suppression of feeding, regulation of blood glucose levels and thermoregulation, thus reinforcing the functional role of central CRF2 in metabolic regulation. The brain loci that mediate the central effects of Ucn 3 remain to be fully determined. Anatomical and functional evidence has suggested that the ventromedial hypothalamus (VMH), where CRF2 is prominently expressed, appears to be instrumental in mediating the effects of Ucn 3 on energy balance, permitting Ucn 3-mediated modulation of feeding and glycemic control. Thus, the Ucn 3-VMH CRF2 system is an important neural pathway in the regulation of energy homeostasis and potentially plays a critical role in energy adaptation in response to metabolic perturbations and stress to maintain energy balance.